Effect of Technology-Enabled Video Instruction on Senior Secondary School Students’ Performance in Selected Technical Drawing Concept in Ilorin - Temitayo Omolara Onasanya; Gboyega Ayodeji Aladesusi; S. A. Taiwo; Samuel Adenubi Onasanya; Jameson Taiwo Adeoye (Indonesian Journal of Educational Research and Technology, 2022)
The study examined the effect of technology-enabled video instruction (TEVI) on senior secondary school students’ performance in selected technical drawing (TD) concepts in Ilorin. The sample for this study consists of an intact class in a senior secondary school in Ilorin. The research adopted a mixed method of quantitative and qualitative research, pre-experimental research of one-group pretest-posttest design. Technology-Enabled Video was used for data collection. The findings from the study revealed that TEVI had a positive effect on the academic performance of students taught selected TD concept, (63.1˃ 51.5), there was a significant difference in the pretest and posttest performance of students taught selected technical drawing concept using TEVI i.e. (df=15, t=-565, p=.000˂0.05). The study concluded that technology-enabled video instruction which is an improvised instructional aid did enhance the academic performance of the students. The study implies that proper integration of technology-based packages like TEVI for instructional delivery will adequately enhance students’ performance. The study Recommended that TEVI should be encouraged among teachers and students, as this will help to boost learners’ interest and provide learners the ability to learn in a direct, self-paced, and individualistic manner, which will, in turn, translate to better academic performance.